THE ROLE OF COST ACCOUNTING IN MANAGING UNUSED CAPACITY AND ACHIEVING OPTIMAL RESOURCE UTILIZATION: A FIELD STUDY IN THE MANUFACTURING SECTOR (World Economics and Finance Bulletin, 2025)
This research aims to demonstrate the role of cost accounting in managing unused capacity and enhancing the optimal utilization of resources in production units, by analyzing the effect of excluding the costs of idle capacity on the accuracy of accounting measurement and the efficiency of managerial decision-making. The study adopted a dual methodology that combined the theoretical aspect through analyzing the concepts related to production capacity and quality costs and the applied aspect, via a field study conducted in one of the plants of the General Company for Electrical and Electronic Industries using data for the years 2023 and 2024. The findings revealed that the utilization rate of practical capacity was very low (less than 10%), leaving more than 90% of available capacity unexploited. This situation resulted in high fixed costs being allocated to products, increased unit costs, and weakened competitiveness. It was also found that excluding unused capacity costs from the unit cost and presenting them as a separate periodic expense enhances the accuracy of accounting information and improves transparency in reporting. Furthermore, the analysis of quality costs indicated that unused capacity can be classified as internal failure costs, and that reducing it requires greater investment in prevention and appraisal costs to minimize waste and improve customer satisfaction
Keywords: Cost Accounting; Unused Capacity; Unit Cost